2021
DOI: 10.3390/molecules26185641
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Pore Development and Formation of Surface Functional Groups in Bamboo-Based Activated Carbon during CO2 Activation

Abstract: Pore development and the formation of oxygen functional groups were studied for activated carbon prepared from bamboo (Bambusa bambos) using a two-step activation with CO2, as functions of carbonization temperature and activation conditions (time and temperature). Results show that activated carbon produced from bamboo contains mostly micropores in the pore size range of 0.65 to 1.4 nm. All porous properties of activated carbons increased with the increase in the activation temperature over the range from 850 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 59 publications
(65 reference statements)
2
12
0
Order By: Relevance
“…The surface area and pore size distribution of an electrocatalyst are important factors that influence the adsorption kinetics employed to measure the diffusion of the adsorbate into the pores. 36,37 surface area of 14.882 m 2 g −1 with a superior total pore volume of 0.1323 cm 3 g −1 as compared with previously reported Co 3 V 2 O 8 nanoparticles. 29 Due to the characteristic feature of mesopores, the prepared Co 3 V 2 O 8 has evenly distributed pore structures on its surface.…”
Section: Physical Characterizationsupporting
confidence: 53%
See 1 more Smart Citation
“…The surface area and pore size distribution of an electrocatalyst are important factors that influence the adsorption kinetics employed to measure the diffusion of the adsorbate into the pores. 36,37 surface area of 14.882 m 2 g −1 with a superior total pore volume of 0.1323 cm 3 g −1 as compared with previously reported Co 3 V 2 O 8 nanoparticles. 29 Due to the characteristic feature of mesopores, the prepared Co 3 V 2 O 8 has evenly distributed pore structures on its surface.…”
Section: Physical Characterizationsupporting
confidence: 53%
“…The surface area and pore size distribution of an electrocatalyst are important factors that influence the adsorption kinetics employed to measure the diffusion of the adsorbate into the pores. 36,37 Fig. 5 illustrates the specific Brunauer–Emmett–Teller (BET) surface area and total pore volume of the Co 3 V 2 O 8 nanofibers, affording a specific surface area of 14.882 m 2 g −1 with a superior total pore volume of 0.1323 cm 3 g −1 as compared with previously reported Co 3 V 2 O 8 nanoparticles.…”
Section: Resultsmentioning
confidence: 89%
“…Ding et al [ 87 ] investigated the effect of different preparation processes on the properties of the materials and found that the material subjected to multi-step activation displayed higher specific surface area (1690 m 2 /g) and pore volume (0.93 cm 3 /g), while one-step activation yielded a relatively high microporosity (72.0%), which is about 1700, 162, and 72 times larger than that of the unactivated materials, respectively. Phothong [ 89 ] and Khuong [ 90 ] investigated the effect of CO 2 activation temperature and activation time on the pore structure of bamboo-derived carbon materials, respectively. The results showed ( Figure 8 b–d) that the carbon material had the maximum microporosity when the activation temperature was 850 °C.…”
Section: Pore Size Regulation Methodsmentioning
confidence: 99%
“… ( a ) Schematic diagram of preparing wood-derived carbon materials by self-activation [ 95 ]; ( b – d ) Impact of temperature on physical activation effect [ 89 ]; ( e – g ) Impact of char/alkali mass ratio on NaHCO 3 activation effect [ 90 ]. …”
Section: Figurementioning
confidence: 99%
“…The mesopore volume was estimated by subtracting the micropore volume from the total pore volume. The pore size distributions of the derived activated carbons were determined from the N 2 adsorption isotherms data by applying the Grand Canonical Monte Carlo (GCMC) simulation [25,28,29]. The average pore size (D av ) was computed based on the equation 4V T /S, where V T is the total pore volume and S is the BET surface area, assuming the pores are cylinder.…”
Section: Characterization Of the Prepared Activated Carbonsmentioning
confidence: 99%